Strategi Implementasi Green Human Resources Management Pada Usaha Mikro, Kecil Dan Menengah (UMKM) Studi Kasus Toko Batik Zahra Malioboro - Maria Nofriyanti; Bangun Putra Prasetya (CV. ITTC INDONESIA, 2024)
This article aims to examine the implementation strategy of Green Human Resources Management (Green HRM) in Micro, Small, and Medium Enterprises (MSMEs). The purpose of this study is to analyze how MSMEs can apply the principles of sustainability in their human resource management The research method used is to use a case study research method with a qualitative approach, data collection is carried out interviews and observations. And the results of the study show that Toko Batik Zahra is not perfect in implementing Green HRM, however Toko Batik Zahra will strive to practice by training and development for employees. there are several benefits of implementing Green HRM, namely by adopting the use of environmentally friendly materials in the production process..